Physiotherapy approach in the lung rehabilitation of COPD patients: an integrative review (Research, Society and Development, 2022)
Physiotherapy hás been acting in various contexts and objectives of pulmonary rehabilitation, acting on symptoms, functional status, adherence to care nad influencing the costs of systemic health, as in the case of Chronic Obstructive Pulmonary Disease (COPD). This integrative review aimed to verify the physiotherapy approach in there habilitation process of patients with COPD. The searches were carried out in the VHL, Scielo, PubMed, PEDro and Google Academic data bases using combination soft He descriptors. We included scientific articles that addressed therese arch objective, published from 2017 to 2022, in Portuguese, English and Spanish, with the full text available for free and that included at least one of the descriptors, and excluded duplicate articles, in other languages which were not selected, books, opinion articles, editorials, theses, dissertations, governmental publications, and/or publications that addressed patients in there habilitation process after COVID-19. With the combinations of descriptors and after applying the eligibility criteria, 6 articles resulted in this review. It was found that physiotherapy has a significant role with in the pulmonary rehabilitation program of these patients and has a broad and essential approach to the program, either by the conducts, assessment tools and/orthe role played in the education of these patients. Parallel to its importance, the physiotherapeutic approach in this scenario and population should continue to advance in research, it is necessary more fieldrese arch with defined protocols that define protocols with in the physiotherapeutic care of pulmonary rehabilitation in patients with COPD.